Classroom action research using student team achievement division approach case study: business process modelling course on bpmn subtopics - Andreswari, R; Syahputra, I (Journal of physics. Conference series, 2019)
Business Process Modeling is a subject that becomes the basis of student of information systems in designing business processes. The purpose of this course is to provide an overview of the analysis of business processes in a specific case study. The results for the odd semester of last year for the Business Process Modeling course showed the results that students' understanding was not satisfactory towards this subject with conventional learning methods. This study designs a learning method with Student Team-Achievement Division (STAD) approach that aims to improve students' understanding of Business Process Modeling Notation (BPMN), both basic and advanced modeling that support Final Assessment and to determine the effect of STAD method on the final grade of Final Assessment in this course. This research stage consists of two cycles. The first cycle activities consist of planning, class action, observation, and analysis and reflection. Activity in cycle two is based on reflection from cycle one divided into redesign, implementation and observation, and reflection. Based on the two cycles that have been done, the positive change is indicated by the increase in the grade of Post Test 2 on Post Test 1. In all study classes there was an increase of 13.12% in class A, 8.01% in class B and 4.82% at class B. This study confirmed that STAD learning method can increase the average grade of class test, increase student participation in learning process such as listening, discussing, asking and expressing opinion. In addition, STAD method is also able to increase the sense of responsibility, cooperation, socialization.